A role for Mitochondrial Rho GTPase 1 (MIRO1) in motility and membrane dynamics of peroxisomes. (20th February 2018) - Castro, Inês G.; Richards, David M.; Metz, Jeremy; Costello, Joseph L.; Passmore, Josiah B.; Schrader, Tina A.; Gouveia, Ana; Ribeiro, Daniela; Schrader, Michael
Abstract : Peroxisomes are dynamic organelles which fulfil essential roles in lipid and ROS metabolism. Peroxisome movement and positioning allows interaction with other organelles and is crucial for their cellular function. In mammalian cells, such movement is microtubule‐dependent and mediated by kinesin and dynein motors. The mechanisms of motor recruitment to peroxisomes are largely unknown, as well as the role this plays in peroxisome membrane dynamics and proliferation. Here, using a combination of microscopy, live‐cell imaging analysis and mathematical modelling, we identify a role for Mitochondrial Rho GTPase 1 (MIRO1) as an adaptor for microtubule‐dependent peroxisome motility in mammalian cells. We show that MIRO1 is targeted to peroxisomes and alters their distribution and motility. Using a peroxisome‐targeted MIRO1 fusion protein, we demonstrate that MIRO1‐mediated pulling forces contribute to peroxisome membrane elongation and proliferation in cellular models of peroxisome disease. Our findings reveal a molecular mechanism for establishing peroxisome‐motor protein associations in mammalian cells and provide new insights into peroxisome membrane dynamics in health and disease. Abstract : Peroxisome motility in mammalian cells is still a poorly understood process, and its physiological importance for organelle function and dynamics is unknown. Here, we show that the Mitochondrial Rho GTPase 1 (MIRO1) is targeted to peroxisomes where it can alter organelle distribution by microtubule‐dependent motility. Expression of this protein in cellular models of peroxisome disease has an impact on peroxisome membrane elongation and division, supporting the notion that motility is an essential element for modulation of the peroxisomal compartment and function.